1980
DOI: 10.1002/jcp.1041040316
|View full text |Cite
|
Sign up to set email alerts
|

Lactate: A major product of glutamine metabolism by human diploid fibroblasts

Abstract: Human diploid fibroblasts metabolize up to 13% of the glutamine in tissue culture medium to lactate. Four microCi of glutamine-U-14C were added to media containing 5 mM or 65 microM glucose or medium containing no added glucose, but supplemented with purine and pyrimidine nucleosides (HGTU). Aliquots of the media were taken at daily intervals and were assayed for glucose, lactate, pyruvate, malate, citrate, aspartate, glutamine, and glutamate. The label incorporation into these compounds was determined, except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
45
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 16 publications
11
45
2
Order By: Relevance
“…15,66,67 As discussed before, glutamine can be oxidized through mitochondria presumably providing cells with substantial amounts of energy in the absence of glucose. 68,69 Consistent with this, our results have demonstrated that inhibiting glycolysis by addition of 2-deoxy-glucose does not affect ATP levels in human fibroblasts. 44 At the same time, glutamine deprivation does not significantly affect the intracellular ATP levels in these cells, 44 indicating that metabolism of each of the nutrients can substitute for the other in maintaining the intracellular ATP level.…”
Section: Why Are Glucose or Glutamine Required For The Survival Of Trsupporting
confidence: 89%
“…15,66,67 As discussed before, glutamine can be oxidized through mitochondria presumably providing cells with substantial amounts of energy in the absence of glucose. 68,69 Consistent with this, our results have demonstrated that inhibiting glycolysis by addition of 2-deoxy-glucose does not affect ATP levels in human fibroblasts. 44 At the same time, glutamine deprivation does not significantly affect the intracellular ATP levels in these cells, 44 indicating that metabolism of each of the nutrients can substitute for the other in maintaining the intracellular ATP level.…”
Section: Why Are Glucose or Glutamine Required For The Survival Of Trsupporting
confidence: 89%
“…The increase in the specific activity of cytosolic GOT during cell growth, together with parallel increases in cytosolic malic enzyme and cytosolic MDH (table II), suggest a greater activity of malate formation/utilization in the cytosol when the cells are at the stationary phase. This is con sistent with our previous observation that malate and aspartate accumulate via these enzyme activities in the presence of 5 mmol/1 glucose mainly during confluence [19].…”
Section: Resultssupporting
confidence: 79%
“…In a previous study, we have reported that human diploid fibroblasts (HDF) metabolize glutamine into lactate and pyruvate, indicat ing an actively functioning pathway for the conversion of 4-carbon tricarboxylic acid (TCA) cycle intermediates to 3-carbon glyco lytic intermediates [19]. Although there have been independent measurements of activities of several of the enzymes involved in this pathway in HDF [1,2, 10-12, 14], no single study has described the activities of these 1 These studies were supported by grants GM 23827 and HD 10982 from the National Institutes of Health.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the observation of significant pyruvate recycling via the action of malic enzyme, the use of uniformly labeled substrate revealed that glutamine did not significantly contribute to lactate formation, due to its comparatively small uptake rate. This is not a universal finding, as glioblastoma cells were shown to metabolize 60% of glutamine to lactate (DeBerardinis et al, 2007), human diploid fibroblasts about 13% (Zielke et al, 1980) and hybridoma cells approximately 9% (Petch and Butler, 1994). Other than the changes observed in the intracellular flux distribution, one of the key difference between the two clones lies in the reduced specific consumption rate of glucose by the PYC-expressing cells.…”
Section: O Henry Y Durocher / Metabolic Engineering ] (]]]]) ]]]-]mentioning
confidence: 99%